2020
DOI: 10.1002/lary.28918
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Fluctuation Revisited

Abstract: Objectives Many patients complain about olfactory fluctuation (OF), which is a symptom commonly attributed to sinonasal disease. Data‐based evidence for its association with sinonasal disease is scarce. The aim of the study is to identify explanatory variables associated with OF and to analyze its predictive value regarding sinonasal disease. Study design We performed a retrospective study based on patients with olfactory dysfunction. Methods We analyzed data from 482 patients attending the smell and taste out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Various hypotheses have been proposed to explain OF; however, the exact mechanism of OF remains unknown. The present study confirms previous findings by Hsieh et al [ 10 ] that self-reported OF is strongly, but not exclusively, associated with sinonasal disorders. In addition to previous studies, our findings show that OF is most frequently observed in sinonasal OD, compared to postviral and idiopathic OD.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Various hypotheses have been proposed to explain OF; however, the exact mechanism of OF remains unknown. The present study confirms previous findings by Hsieh et al [ 10 ] that self-reported OF is strongly, but not exclusively, associated with sinonasal disorders. In addition to previous studies, our findings show that OF is most frequently observed in sinonasal OD, compared to postviral and idiopathic OD.…”
Section: Discussionsupporting
confidence: 93%
“…The pathophysiology of sinonasal OD involves an impairment of nasal airflow and inflammation of the olfactory neural pathway [ 10 , 11 , 15 , 16 ]. Airflow to the olfactory region was found to increase when airway patency improved at critical areas, such as the olfactory cleft and the internal nasal valve [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRS is often associated with a fluctuating course of the disease, which can even lead to daily differences in symptom severity. 11 Not surprisingly, daily diaries-"real-life assessment of CRS patients" 12,13 -have been proposed to gain greater insights into the main drivers of CRS symptomatology. However, completing these symptom diaries on a daily basis might impose a significant respondent burden, leading to nonadherence with data collection protocols.…”
Section: Introductionmentioning
confidence: 99%
“…CRS is often associated with a fluctuating course of the disease, which can even lead to daily differences in symptom severity 11 . Not surprisingly, daily diaries—“real‐life assessment of CRS patients” 12,13 —have been proposed to gain greater insights into the main drivers of CRS symptomatology.…”
Section: Introductionmentioning
confidence: 99%